Administration of cyclosporine A in pregnant rats: the effect on blood pressure and on the glomerular number in their offspring - Słabiak-Błaz, Natalia; Adamczak, Marcin; Gut, Nadezda; Grajoszek, Aniela; Nyengaard, Jens R.; Ritz, Eberhard; Wiecek, Andrzej (Kidney & blood pressure research, 2015)
Background/Aims: Cyclosporine A (CsA) is a commonly used immunosuppressive agent. In some patients treatment with CsA has to be continued during pregnancy. The aim of the study was to assess in an experimental model whether the exposure to CsA during fetal life influences the number and volume of glomeruli, kidney function and blood pressure in the offspring. Methods:Eight pregnant female Sprague-Dawley rats were allocated to 2 treatment regimens: with CsA or solvent. Blood pressure was measured in the offspring at 7 and 11 weeks of age and albuminuria was determined at 11 weeks of age. In the kidney the number and mean volume of glomeruli was assessed using stereological methods. Results: In the offspring of pregnant rats treated with CsA the number of glomeruli was significantly lower and the mean volume of glomeruli was higher when compared to the offspring of pregnant rats receiving solvent. Systolic and diastolic blood pressures as well as albuminuria were significantly higher in the offspring of mothers treated with CsA during gestation compared to the offspring from the control group. Conclusions: Exposure of rats to CsA during fetal life impairs kidney development, thus potentially predisposing to chronic kidney disease and hypertension in the adult life.
Gesehen am 18.06.2020